Rare presentation of inflammatory myofibroblastic tumor as intussusception in a child with idiopathic aplastic anemia - Ashok Kumar Sharma; Satyendra Katewa (Wolters Kluwer Medknow Publications, 2022)
Inflammatory myofibroblastic tumor (IMT) is an uncommon mesenchymal solid tumor documented in children and young adults. A 7-year-old boy diagnosed case of acquired aplastic anemia, referred to our hospital for hematopoietic stem cell transplantation. He was admitted to the hospital with febrile neutropenia. Blood culture showed persistent Escherichia coli infection. During hospital stay, he had bilious vomiting with tender abdomen suggestive of subacute intestional obstruction. Computed tomography of the abdomen was suggestive of ileocolic intussusception. Emergency laparotomy done which revealed a large polypoid mass involving cecum and part of ascending colon with ileocolic intussusception, child underwent ileotransverse colon resection with end-to-side anastomosis. Immunohistochemistry was suggestive of IMT. The child had persistent fever and protracted course during hospital stay and finally died. E. coli sepsis is associated with IMT and leads to protracted course in immunosuppressed patients such as aplastic anemia. As the imaging and laboratory tests are nonspecific, it should be considered in an immunocompromised children who have E. coli sepsis and abdominal complaints and rare presentation as intussusception.